COMMUNICATION STRATEGY IMPLEMENTATION OF RADIO STATIONS WITH COMBINED INTERNET NEW MEDIA (Case Study at PT. Radio Tjandra Buana Suara FM Cianjur) - Jamilah, Jamilah; Sri Utami, Yessi; Kurniadi, Endrian; Sinta Lestari, Dewi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
This study aims to determine the strategy implementation process in dealing with media convergence. Radio Tjandra FM has developed from what was originally limited to conventional radio but later developed by combining it with new media such as the internet. The basis of the theory used isNew media by Pierre Levy. This study uses a qualitative research method with a case study approach. In its implementation, Radio Tjandra no longer only broadcastson air on radio but also take advantage of internet media as a process of expanding listeners, increasing existence and also displaying advertisements, what is done is to create social media accounts such as Facebook, Twitter, Instagram, creating streaming radio websites and applications. Apart from that, Radio Tjandra also carries out a lot of off air or on air activities in crowded places using the OB Van. The results of the process of implementing the strategy of merging radio with the internet have not yet yielded maximum results for expanding advertising, but for expanding listening it is sufficient to provide significant results, as evidenced by the increase listeners every day. So the challenge going forward for Tjandra FM Radio is how to find new, more interesting innovations, and also develop existing human resources so that the initial vision and mission can be achieved and the radio's existence increases.